Soft three-dimensional network materials with rational bio-mimetic designs - Dongjia Yan (Nature Portfolio, 2020)
The development of artificial 3D soft materials and device systems that can reproduce the nonlinear, anisotropic mechanical properties of biological tissues remains challenging. Here, the authors design a class of soft 3D network materials that can offer defect-insensitive, nonlinear mechanical responses closely matched with those of biological tissues.